2015
DOI: 10.5433/1679-0359.2015v36n2p889
|View full text |Cite
|
Sign up to set email alerts
|

Helminths parasites of stray dogs (Canis lupus familiaris) from Cuiabá, Midwestern of Brazil

Abstract: Helminths cause respiratory and gastrointestinal infections in animals, especially in neonates and young animals. Some species of helminth parasites of domestic animals have zoonotic potential, becoming a public health problem, especially when combined with lack of information about the population of these zoonosis and lack of control over of their hosts. This study aimed to identify and quantify the species of helminths from dogs that are not domiciled in the region of Cuiabá, in the Midwest region of Brazil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…However, it is also a zoonotic pathogen of certain danger to human health (Hall & Sonnenberg, 1956;Singh et al, 1993;Mohd-Shaharuddin et al, 2019). This species is also common in the domestic dog (Canis lupus familiaris) in most of the world (Ramos et al, 2015;Scaramozzino et al, 2018;Opazo et al, 2019). Thus, human infection with T. vulpis is a matter of considerable importance since dogs are not only domestic pets but helpers of humans (Kenney & Eveland, 1978;Kenney & Yermakov, 1980;Dunn et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also a zoonotic pathogen of certain danger to human health (Hall & Sonnenberg, 1956;Singh et al, 1993;Mohd-Shaharuddin et al, 2019). This species is also common in the domestic dog (Canis lupus familiaris) in most of the world (Ramos et al, 2015;Scaramozzino et al, 2018;Opazo et al, 2019). Thus, human infection with T. vulpis is a matter of considerable importance since dogs are not only domestic pets but helpers of humans (Kenney & Eveland, 1978;Kenney & Yermakov, 1980;Dunn et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This species is common in domestic dog (Canis lupus familiaris Linnaeus, 1758) populations. For example, 43% of examined dogs in Brazil were infected with T. vulpis, the abundance index was 10.03, with intensity of infection ranging 1 to 181 nematode specimens (Ramos et al, 2015). In various regions of Italy, prevalence of this nematode species in dogs ranged 5.8% to 11.1% (Zanzani et al, 2014;Scaramozzino et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…From a total of 271 examined dogs, only four (1·47%) were found to be positive for A. caninum, while several studies including those from northwestern Tunisia and other parts of the world, have shown A. caninum to be the most widespread of all hookworms (Lahmar et al 2001;Bajalan, 2010;Mateus et al 2014;Emamapour et al 2015;Ramos et al 2015;Ilić et al 2017;Pumidonming et al 2017). Few cases of presumed human infection with T. vulpis causing visceral larva migrans syndrome and/or intestinal infections have been reported (Díaz-Anaya et al 2015;Ilić et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The role of dogs in the spread of diseases that pose a potential risk to public health has been reported by many authors (Bentounsi et al 2009;Jenkins et al 2014;Ramos et al 2015;Amissah-Reynolds et al 2016;Geraili et al 2016;Ilić et al 2017;Dakkak et al 2017). Dogs are known definitive hosts of several helminths and as such contaminate the environment with infective and/or parasitic stages that undergo maturation in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Humans and felines, which may be accidental hosts, are more susceptible to infection in areas with high prevalence of the canine disease (Garcez et al 2006, Mirahmadi et al 2017, which is distributed all over the globe (Bolio-Gonzalez et al 2007, Bowman & Atkins 2009, Hou et al 2011, Simsek et al 2011, Montoya-Alonso et al 2015, Bendas et al 2017. It has been found in every geographical region of Brazil, with prevalence rates over the last decade ranging from 2.1% in Florianópolis, in the Southern state of Santa Catarina (SC), to 62.2% in Armação de Búzios, in the Southeastern state of Rio de Janeiro (RJ) (Silva et al 2008, Dirofilaria immitis infection in dogs in Algodoal Island, Brazilian Amazon Furtado et al 2009, Ogawa et al 2013, Labarthe et al 2014, Soares et al 2014, Ramos et al 2015.…”
Section: Introductionmentioning
confidence: 99%